New dynamic bandwidth allocation algorithm based fuzzy-logic for ethernet PON - Radzi N.A.Mohd.; Din N.Md.; Mustafa I.S.; Sadon S.Kh.; Al-Mansoori M.H. (2023)
We proposed a fuzzy-logic-based dynamic bandwidth allocation (FLDBA) algorithm for upstream Ethernet passive optical network (EPON). In the proposed DBA algorithm, the optical line terminal allocates bandwidth to the optical network units in proportion to the priority category of the traffic class. Simulations were performed to prove the accuracy of the FLDBA algorithm by comparing the algorithm with a previous DBA algorithm, Min's DBA algorithm that is an enhancement from interleaved polling with adaptive cycle time. The results show significant performance, as high as 20% improvements in terms of the bandwidth utilization, delay and the fairness. 2009 IEEE.